Biochar amendment to soil changes dissolved organic matter content and composition. (January 2016) - Smebye, Andreas; Alling, Vanja; Vogt, Rolf D.; Gadmar, Tone C.; Mulder, Jan; Cornelissen, Gerard; Hale, Sarah E.
Highlights: Biochar increased the pH and released dissolved organic matter from the soil. Biochar sorbed more small aliphatic than large aromatic dissolved organic molecules. A size exclusion effect in biochar's micropores could explain the sorption pattern. Abstract: Amendments of biochar, a product of pyrolysis of biomass, have been shown to increase fertility of acidic soils by enhancing soil properties such as pH, cation-exchange-capacity and water-holding-capacity. These parameters are important in the context of natural organic matter contained in soils, of which dissolved organic matter (DOM) is the mobile and most bioavailable fraction. The effect of biochar on the content and composition of DOM in soils has received little research attention. This study focuses on the effects of amendments of two different biochars to an acidic acrisol and a pH-neutral brown soil. A batch experiment showed that mixing biochar with the acrisols at a 10 wt.% dose increased the pH from 4.9 to 8.7, and this resulted in a 15-fold increase in the dissolved organic carbon concentration (from 4.5 to 69 mg L −1 ). The pH-increase followed the same trend as the release of DOM in the experiment, causing higher DOM solubility and desorption of DOM from mineral sites. The binding to biochar of several well-characterised reference DOM materials was also investigated and results showed a higher sorption of aliphatic DOM to biochar than aromatic DOM, with DOM-water partitioning coefficients ( K d -values) ranging from 0.2 to 590 L kg −1 . A size exclusion occurring in biochar's micropores, could result in a higher sorption of smaller aliphatic DOM molecules than larger aromatic ones. These findings indicate that biochar could increase the leaching of DOM from soil, as well as change the DOM composition towards molecules with a larger size and higher aromaticity.